Top quark mass measurement using the template method at CDF - Aaltonen, T; Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We present a measurement of the top quark mass in the lepton+jets and dilepton channels of tt̄ decays using the data sample corresponding to an integrated luminosity of 5.6fb-1 of pp̄ collisions at Tevatron with √s=1.96TeV, collected with the CDF II detector. We construct templates of two reconstructed top quark masses from different jets-to-quarks combinations and the invariant mass of two jets from the W decays in the lepton+jets channel, and a reconstructed top quark mass and mT2, a variable related to the transverse mass in events with two missing particles, in the dilepton channel. The simultaneous fit of the templates from signal and background events in the lepton+jets and dilepton channels to the data yields a measured top quark mass of Mtop=172.1±1.1(stat)±0. 9(syst)GeV/c2. © 2011 American Physical Society.